Penguatan Manajemen Keuangan UMKM Batik Solo melalui Pelatihan dan Penyuluhan Berkelanjutan - Mariana Mariana; Yudhy Widya Kusumo; Sri Winarsih Ramadana; Rahmaniar Rahmaniar; Rahmad Rahmad; Nurul Kamaliah (LPPM Universitas Timor, 2025)
Batik, as a traditional Indonesian art form that has developed over centuries, gained international recognition when it was designated as an Intangible Cultural Heritage by UNESCO in 2009. Despite its high cultural and historical value, MSMEs in the batik sector in Solo face several challenges, particularly related to financial management and access to capital. The potential of batik MSMEs has not been fully utilized due to a lack of knowledge in financial management and a low awareness of the importance of proper financial management. To address these issues, community service was conducted using lectures and practical training methods at strategic locations such as Batik Wijaya Kusuma and Batik Danny. The materials covered included basic transaction recording, budgeting, and cash flow management. The results showed that the outreach and training activities received positive responses and could provide an effective solution to improve the financial management of batik MSMEs. Therefore, this activity should be carried out continuously to support the improvement of financial performance in batik MSMEs in Solo.